Cytomegalovirus Infection as Risk of Atherogenic Lipid Profile in Iraqi Aborted Women - hanna, Dalya Basil; waheed, Huda Jaber; ali, Zahraa Qasim; khaleq, Maysaa Ali Abdul (Bangladesh Journal of Medicine, 2020)
Introducion: Atherosclerosis is a form of the cardiovascular diseases which may occur due to a chronic inflammatory reaction to endothelial damage caused by multiple causes which include infection by microorganisms like Cytomegalovirus (CMV). Methods: The present study aims to evaluate the effect of cytomegalovirus infection in patients and its relation to atherosclerosis and to measure the monocyte chemoattractant protein-1 (MCP-1) as a predictive marker for inflammatory process. A total of 30 women who were attending the Gynecology outpatient clinics and were suffering from abortion for first time or with recurrent abortion due to CMV infection were enrolled in the current study. For comparison, twenty blood samples were collected from healthy apparent women as a control group in this study. Serum MCP-1, IL-6 and CMV-IgM were measured by using ELISA technique. Lipid profile which includes total cholesterol, triglycerides, high density lipoprotein (HDL), and low density lipoprotein (LDL) was measured by spectrophotometer. Results: The results of this study showed a significant difference in mean of IL-6 in patients was (570.67 ± 199.27) when compared to control group (pÃ0.0001). While there is no significant difference of MCP-1 level between patients and control group (P=0.134). And the results showed a significant elevation of cholesterol (P<0.05) and a highly significant elevation of triglyceride and LDL in CMV infected patients (P<0.01), while no elevation occurred in HDL values (P=0.977). Conclusion: According to the present data there is a correlation between CMV infection and atherosclerosis. Bangladesh J Medicine July 2020; 31(2) : 47-51